The integration between strategic cost management techniques to improve the performance of Iraqi manufacturing companies - Al-Naser, Khalis Hasan Yousif; Mohamed, Rapiah (Macrothink Institute, 2017)
The performance of manufacturing industry in Iraq has been declining over the last few decades.Worst still, many companies in the manufacturing sector in Iraq are yet to adopt Balanced Scorecard (BSC) to improve their performance despite its potency ensure to achieve competitive advantage and better performance.This study examines the integration between Total Quality Management (TQM) and BSC four perspectives in Iraqi manufacturing industry. Data were collected by means of structured questionnaire survey using simple random sampling and a Partial Least Squares (PLS) algorithm and bootstrap techniques were used to test the hypothesis of the paper.The result revealed that TQM had a significant positive effect on BSC through the measurement of customer perspective, financial perspective, innovation and learning perspective, and internal business process perspective.The finding implies that Iraqi manufacturing industries can attain the performance of their companies in the different perspective of BSC by proper implementation of TQM technique.